2013
DOI: 10.1007/978-3-642-39038-8_3
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Reuse with Compiled Domain-Specific Languages

Abstract: Programmers who need high performance currently rely on low-level, architecture-specific programming models (e.g. OpenMP for CMPs, CUDA for GPUs, MPI for clusters). Performance optimization with these frameworks usually requires expertise in the specific programming model and a deep understanding of the target architecture. Domain-specific languages (DSLs) are a promising alternative, allowing compilers to map problem-specific abstractions directly to low-level architecture-specific programming models. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 27 publications
0
36
0
Order By: Relevance
“…DSLs developed through Delite have been shown to perform competitively with hand-optimized C code. For graph processing, the Opti-Graph DSL 23 (embedded in Scala) performs on par with the standalone language Green Marl. Many Scala features are crucial for LMS and Delite to implement compiler optimizations in a modular and extensible way.…”
Section: Resultsmentioning
confidence: 99%
“…DSLs developed through Delite have been shown to perform competitively with hand-optimized C code. For graph processing, the Opti-Graph DSL 23 (embedded in Scala) performs on par with the standalone language Green Marl. Many Scala features are crucial for LMS and Delite to implement compiler optimizations in a modular and extensible way.…”
Section: Resultsmentioning
confidence: 99%
“…To mitigate this, we need principled ways of inter-operating between performanceoriented DSLs. We have recently shown that Delite DSLs can be composed at different granularities by exploiting the common back-end framework [Sujeeth et al 2013b]. However, this composition is limited (for DSLs with restricted semantics, we allow only pipeline composition), and does not address composing DSL front-ends (e.g., grammars or type systems).…”
Section: Discussionmentioning
confidence: 99%
“…Sujeeth et al first presented these DSLs [Sujeeth et al , 2013b; we expand on this discussion by highlighting Delite components that were reused in the implementation of the DSLs and identifying new features that had to be added to the framework to support a particular DSL. We also show how Delite supports implementing nontrivial domain-specific analyses and transformations for OptiMesh.…”
Section: Dslsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other systems include PetaBricks [3], CVXgen [35] and Halide [65,64]. Delite is a compiler framework for embedded DSLs that provides parallelization and heterogeneous code generation on top of LMS [73,13,74,50,82]. Related work on lowlevel systems oriented programming in high-level languages in-cludes [32] and the Singularity operating system [49], the LegoBase database engine [47], and staged parsers for communication protocols [43].…”
Section: Related Workmentioning
confidence: 99%